Expression and regulation of cryopyrin and related proteins in rheumatoid arthritis synovium. Issue 5 (21st October 2004) - Rosengren, S; Hoffman, H M; Bugbee, W; Boyle, D L
Abstract : Background: Rheumatoid arthritis (RA) synovium is characterised by enhanced NF-κB activity and proinflammatory cytokines. Cryopyrin (CIAS-1, NALP-3, PYPAF-1) has been shown to regulate NF-κB and caspase-1 activation. Objective: To study the expression of cryopyrin, its effector molecule ASC, and its putative antagonist pyrin in RA and osteoarthritis (OA) synovium, and the main two cellular constituents of synovial lining, cultured fibroblast-like synoviocytes (FLS) and macrophages. Methods: FLS and macrophages were cultured in the presence of inflammatory mediators. Real time polymerase chain reaction was used to quantify message levels in synovial biopsy specimens and cells. In situ hybridisation was employed to localise expression of cryopyrin mRNA. Results: Cryopyrin mRNA was raised in RA synovium and detected in both lining and sublining regions. FLS from RA and OA tissue expressed low baseline levels of cryopyrin transcripts that were induced by tumour necrosis factor α (TNFα). In contrast, macrophages differentiated in vitro expressed relatively high cryopyrin levels, which were further induced by TNFα, but not by interleukin 1β. ASC mRNA levels were comparable in RA and OA tissue, FLS, and macrophages, and were depressed by TNFα in macrophages. Pyrin expression was higher in RA synovium than in OA tissue, and virtually undetectable in FLS but high in macrophages where it was unchanged by TNFα treatment. Conclusion: These results suggest that enhanced cryopyrin levels in RA synovium are due to a greater numbers of tissue macrophages, and demonstrate transcriptional regulation of cryopyrin in a chronic inflammatory disease.